Challenging Management of a Patient With Severe Bilateral Deep Vein Thrombosis. (March 2020) - Hamandi, Mohanad; Lanfear, Allison T.; Woolbert, Seth; Bolin, Madison L.; Fan, Joy; William, Michael; Khan, Zoheb; DiMaio, J. Michael; Dib, Chadi
Among patients with proximal iliofemoral deep vein thrombosis (DVT) and an elevated Villalta score, anticoagulation therapy alone may not be a sufficient management strategy in select cases. In this article, we report a case of severe bilateral iliofemoral DVT that resisted the standard treatment for DVT, requiring catheter-directed thrombolysis and subsequent mechanical thrombectomy.